Is there room for geoengineering in the optimal climate policy mix?. Issue 48 (April 2015) - Bahn, Olivier; Chesney, Marc; Gheyssens, Jonathan; Knutti, Reto; Pana, Anca Claudia
Abstract : Highlights: We investigate the optimal policy mix for dealing with climate change. We consider jointly mitigation, adaptation, and solar radiation management (SRM). SRM can control temperature, but brings environmental side-effects. SRM is not robust due to uncertainty in magnitude and persistency of side-effects. Implementing SRM with wrong assumptions about side-effects largely decreases welfare. Abstract: We investigate geoengineering as a possible substitute for mitigation and adaptation measures to address climate change. Relying on an integrated assessment model, we distinguish between the effects of solar radiation management (SRM) on atmospheric temperature levels and its side-effects on the environment. The optimal climate portfolio is a mix of mitigation, adaptation, and SRM. When accounting for uncertainty in the magnitude of SRM side-effects and their persistency over time, we show that the SRM option lacks robustness. We then analyse the welfare consequences of basing the SRM decision on wrong assumptions about its side-effects, and show that total output losses are considerable and increase with the error horizon. This reinforces the need to balance the policy portfolio in favour of mitigation.